TOWARDS AN UNDERSTANDING OF MINISTERIAL PRIESTHOOD IN THE LIGHT OF PRIESTHOOD OF THE BAPTIZED - Leo Andoh Korsah; Francis Appiah-Kubi (Asian Horizons, 2015)
The renaissance of the doctrine of priesthood of the baptized since the Second Vatican Council and the emphasis on the royal priesthood of all Christians from Protestant tradition have led to the emergence of vibrancy and sometimes over zealousness among the laity especially in Anglophone West African Countries. This religious phenomenon appears to put into question, from the pastoral perspective the nature of the ministerial priesthood. From the fourth century to the present age, the priest has always been considered as a person endowed withpower to preside over the ucharistic sacrifice and administer the Sacraments. The theology of the ministerial priesthood is basically Christological. At ordination, the priest takes on a character that configures him to Christ and acts in the person of Christ in his triple priestly function as a Sanctifier, Teacher and a King. This article tries to emphasize the distinctiveness of the ministerial from the baptismal priesthood. It traces its historical development from theologicalperspective. The ordained priests perform sacerdotal functions by offering the sacrifice of the Holy Mass, while the faithful exercise their priesthood in “receiving the sacraments, in prayer and thanksgiving, in the witness of a holy life, and by self-denial and active charity” (LG, 10).